Borrelia burgdorferi in an urban environment: white-tailed deer with infected ticks and antibodies. - Magnarelli, L A (1995)
Ticks and blood samples were collected from white-tailed deer (Odocoileus virginianus) in forests located in an insular, urban area of Bridgeport, Conn., and in rural south central Connecticut during 1992 and 1993. Immature and adult Ixodes scapularis ticks were tested for Borrelia burgdorferi, the etiologic agent of Lyme borreliosis, by indirect fluorescent-antibody staining methods. Deer sera were analyzed for antibodies to this bacterium by an enzyme-linked immunosorbent assay. Infected ticks parasitized deer in Bridgeport from May through December; the prevalence of infection varied from 1.1% of 93 larvae to 28.1% of 114 adult females. The percentages of infected males (10.5% of 380 ticks) and females (13.7% of 328 ticks) were relatively lower in south central Connecticut. In antibody tests, the prevalence of seropositive specimens collected in Bridgeport (61% of 146 serum specimens) was more than twofold greater than that of specimens obtained in south central Connecticut (26.7% of 116 serum specimens). Foci for Lyme borreliosis can occur in forested, urban settings as well as in rural areas if there are ticks, rodents, birds, and large mammals present. Human exposure to ticks in such sites should be considered as a possible source of B. burgdorferi infection.